Radio Propagation Measurements In Brazil: Clear Air and Rainfall EffectsDOI: 10.14209/jcis.1994.2 - A.R. da Silva Mello, L.; S. Pontes, M.; R. Dhein, N.; M. Einloft, C. (Journal of Communication and Information Systems, 2015)
Methods for the prediction of propagation effect in radio communications systems are usually semiempirical and dependent on the statistical behaviour of radiometeorological parameters, such as refractivity gradient and rainfall rate. The data basis currently available for the development, testing and application of these methods have been obtained, mostly, on experiments performed at sites in temperate climates. In the last 15 years several propagation measurements' campaigns have been carried out in Brazil, aiming to provide data for the development and application of prediction methods in tropical and equatorial climates. In this paper, results from these experiments are reviewed and new data made available in experiments now underway are presented.